Cultivating healthcare innovators: a cross-sectional study on entrepreneurial abilities and influencing factors among nursing undergraduates - Hongyu Yu; Guimin Wen (BMC Nursing)
Abstract Background The rapid transformation of healthcare environments, intensifying employment competition, and emerging entrepreneurial opportunities in healthcare highlight entrepreneurial ability as an essential quality for nursing undergraduates to address professional challenges. Current educational systems inadequately cultivate critical entrepreneurial skills, and research in this area remains scarce. A systematic evaluation of their entrepreneurial abilities and influencing factors is urgently needed to bridge the education-practice gap and empower nursing professionals to drive innovation-driven development in healthcare. Objectives To assess nursing undergraduates’entrepreneurial abilities, identify influencing factors, and propose actionable strategies to enhance innovation-driven adaptability, supporting healthcare transformation and evidence-based education policies. Methods A cross-sectional survey was conducted at the nursing school of a university. Data was collected from 521 undergraduate nursing students using convenience sampling from March to April 2023. The Self-Assessment Scale for Entrepreneurial Ability of College Students was used to assess the entrepreneurial abilities of participants. A multiple linear regression was performed to identify factors related to entrepreneurial abilities. Results The mean score of nursing undergraduates’ entrepreneurial abilities was 3.80 (SD = 0.647). Among the sub-dimensions, social coping abilities scored the highest (3.92, SD = 0.663), while basic entrepreneurial abilities had the lowest score (3.69, SD = 0.740). Independent t-tests and ANOVA revealed higher entrepreneurial competency scores among nursing undergraduates with: Higher comprehensive academic performance rankings, Only-child status, urban family residence, parents holding college or associate degrees, class leadership experience, practical social experience, entrepreneurial exposure, participation in entrepreneurship-related competitions/lectures/forums, awareness of national entrepreneurship policies, and neutral family attitudes toward entrepreneurship.Multiple linear regression analysis reveals that comprehensive academic performance rankings, class leadership experience, parents’ educational level, and family members’ attitudes towards entrepreneurship significantly influence their entrepreneurial abilities (p-value = 0.000), accounting for 19.3% of the total variance. Conclusions These findings underscore the need to integrate targeted entrepreneurship training—particularly in opportunity identification, risk management, and resource mobilization—into nursing curricula to address skill gaps. Future research should explore longitudinal impacts of educational interventions, cross-cultural comparisons of entrepreneurial competency frameworks, and the role of institutional policies in fostering healthcare innovation. Practically, this study advocates for policy reforms that incentivize experiential learning (e.g., entrepreneurship practicums) and family engagement programs to align educational outcomes with evolving healthcare demands.